Creation of a restrictive atrial communication in pulmonary arterial hypertension (PAH): effective palliation of syncope and end‐stage heart failure. (1st June 2018) - Bauer, Anna; Khalil, Markus; Schmidt, Dorle; Bauer, Jürgen; Esmaeili, Anoosh; Apitz, Christian; Voelkel, Norbert F.; Schranz, Dietmar
Abstract : Atrial septostomy (AS) is recommended for pulmonary arterial hypertension (PAH)‐associated right ventricular (RV) failure, recurrent syncope, or pulmonary hypertensive crisis (PHC). We aimed to evaluate the feasibility and efficacy of AS to manage PAH from infancy to adulthood. From June 2009 to December 2016, transcatheter atrial communications were created in 11 PAH patients (4 girls/women; median age = 4.3 years; range = 33 days–26 years; median body weight = 14 kg; range = 3–71 kg; NYHA‐/Ross class IV; n = 11). PAH was classified as idiopathic (n = 6) or secondary (n = 5). History of syncope was dominant (n = 6); two with patent foramen ovale (PFO) admitted with recurrent PHC, three patients required resuscitation before AS. Three patients had PAH‐associated low cardiac output. The average pulmonary arterial pressures (PAP systolic/diastolic) were 101/50 (±34/23); the corresponding systemic arterial pressures (SAP) were 99/54 (±23/11); and the mean ratio of PAPd / SAPd was 0.97 (±0.4). Percutaneous trans‐septal puncture was uneventfully performed in nine patients; a PFO was dilated in two patients. There was no procedure‐related mortality. The median balloon size was 10 mm (range = 6–14 mm); the mean catheter time was 174.6 ± 48 min; fluoroscopy time was 19.8 (±11) min. Syncope and PHC were successfully treated in all patients. The mean arterial oxygen saturation decreased from 97 ± 2 to 89 ± 11.7. One patient died awaiting lung transplantation, one continues to be listed; two patients received a reverse Potts‐shunt, one patient died during follow‐up; seven patients are stable with PAH‐specific treatment. Percutaneous AS is an effective method palliating PAH‐associated syncope, PHCs or right (bi‐) ventricular heart failure.